Brain abscess and cervical lymphadenitis due to Paraclostridium bifermentans: A report of two cases. (June 2018) - Sankar R, Udhaya; Biswas, Rakhi; Raja, S.; Sistla, Sujatha; Gopalakrishnan, M.S.; Saxena, Sunil Kumar
Abstract: Paraclostridium bifermentans (current nomenclature of Clostridium bifermentans since 2016) is a gram-positive, spore-forming anaerobic bacterium. Here, we describe two cases associated with this organism. The first, primarily a case of tubercular brain abscess where P. bifermentans was isolated as part of a polymicrobial flora, following a neurosurgical procedure for the same and the second, a case of cervical lymphadenitis from which it was isolated as the sole causative agent. There are only a few reported cases of P. bifermentans in literature and these cases illustrate the widening spectrum of infections related to it. Highlights: First case report of cervical lymphadenitis due to Paraclostridium bifermentans . Paraclostridium bifermentans isolated from a case of brain abscess, as a part of polymicrobial causation. Pathogenic potential of Paralostridium bifermentans needs to be evaluated.